2017
DOI: 10.17850/njg97-1-02
|View full text |Cite
|
Sign up to set email alerts
|

3D restoration of a Cretaceous rift basin in Kilen, eastern North Greenland

Abstract: The semi-nunatak Kilen is a key area to understand the setting of the Cretaceous sedimentary basin in eastern North Greenland. The basin geometry has been obscured by later N-S compression and inversion of presumable Palaeocene-Eocene age. A 3D restoration of the Cretaceous basin is presented based on new oblique photogrammetry and field data combined with published data. The 3D restoration focuses on the main faults and a well constrained mid-Cretaceous horizon. The restoration shows that the horizon was offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Several Cretaceous intervals and units were poorly dated or not dated at all. The succession has been subject to significant thermal influence, which has removed organic palynomorphs hampering the use of dinoflagellate cysts stratigraphy (Håkansson & Pedersen 2001;Svennevig et al 2017;Pedersen et al 2018). Macrofossils are absent or scarce and poorly preserved in several units.…”
Section: Wwwgeusbulletinorgmentioning
confidence: 99%
See 2 more Smart Citations
“…Several Cretaceous intervals and units were poorly dated or not dated at all. The succession has been subject to significant thermal influence, which has removed organic palynomorphs hampering the use of dinoflagellate cysts stratigraphy (Håkansson & Pedersen 2001;Svennevig et al 2017;Pedersen et al 2018). Macrofossils are absent or scarce and poorly preserved in several units.…”
Section: Wwwgeusbulletinorgmentioning
confidence: 99%
“…Parallel to the biostratigraphic and lithostratigraphic work, the structural geology of Kilen was revised based on mapping from oblique photogrammetry and field work (Svennevig et al 2015). A new structural model for Kilen was published, in which it was shown that Late Cretaceous extension caused normal faulting followed by Eurekan compression, which gave rise to folding and thrusting (Svennevig et al 2016(Svennevig et al , 2017.…”
Section: Wwwgeusbulletinorgmentioning
confidence: 99%
See 1 more Smart Citation
“…(2010) and Svennevig et al. (2017). The dashed red line delineates the inferred Barremian coastline position off Greenland and Svalbard, modified after Grundvåg et al.…”
Section: Introductionmentioning
confidence: 96%
“…Location of the study area in eastern North Greenland on a pre‐break‐up Cretaceous plate reconstruction (Müller et al., 2016, as modified by Svennevig et al., 2017) with Jurassic–Lower Cretaceous structural features from Faleide et al. (2010) and Svennevig et al.…”
Section: Introductionmentioning
confidence: 99%